(untitled) (UNWE Yearbook, 2020)
Sport is long-year educational-training process, building many qualities in those practicing it, such as will, tenacity, persistency, responsibility, self-confidence, discipline. It helps maintaining good health and discharges the psychic tension. School and universities are the places for attractive contacts, forming of knowledge and skills and preparation of the persons under education for future realization at the labour market.In the world of modern technologies and social nets, there is no other area in life except sport activity giving exclusive possibility for close, tet a tet association, for building of social contacts and forming up of social groups.In this article we consider the possibilities the sport really grants to the contestants from the UNWE team, for improvement of their social status and role in the society.The role of sport as a means for leading a healthy way of life, especially in the universities should be directed in another direction – creating of wide circle of contacts, building of motivation and responsibility for achievement of the tasks set, focusing on the achievements. Higher education is a possibility for young people to associate together and develop in a homogeneous environment, of similar interests, to create contacts, allowing them to realize on the labour market in future.60% of the inquired persons deem that futsal practicing in UNWE has helped for improvement of their social status, manifested in the bigger number of social contacts, better health condition and increased self-confidence, leader’s role in the society and financial prosperity